Rice farmers’ knowledge, attitudes and practices towards mosquitoes in irrigation schemes in Côte d’Ivoire: a qualitative study - Kallista Chan; Kouadio Aimé-Charles Konan; Dimi Théodore Doudou; Ghislain Brou Kouadio; Jo Lines; Robert Aunger; Raphael N’Guessan; Lucy S. Tusting (Malaria Journal, 2023)
Abstract Background Irrigated rice cultivation in sub-Saharan Africa not only brings more malaria vectors to nearby communities, but also greater malaria risk. To aid the implementation of mosquito control in rice-growing communities, it is necessary to understand how farmers understand, view and manage their responsibility in mosquito generation and whether they are interested in coordinating to minimize it. Methods Qualitative methods (observation grids, semi-structured in-depth interviews and focus group discussions) were used to reveal the perceptions of mosquitoes and their control in two irrigated rice farming communities in central Côte d’Ivoire near the M’bé and Lokapli irrigation schemes. Results All rice farmers viewed mosquitoes as severe nuisances, and most acknowledged that they caused djèkouadjo (malaria) and were less numerous during harmattan (dry season). Many study participants believed that mosquitoes originated from grasses and stagnant water around villages. Only those living closer in proximity (~ 1 km) to the paddies believed that mosquitoes came from the bas-fonds (irrigated lowlands). However, they did not associate mosquito production with rice cultivation. Some farmers believed that there were more mosquitoes in recent years than historically because of the dam construction, but remarked on the importance of the dam (and bas-fonds) for their livelihood. Many farmers were not convinced that mosquito control could occur at farm-level. Conclusions To enhance accountability amongst rice farmers, there is a need for greater awareness on the rice-mosquito link, and emphasis that the link does not imply a trade-off between food production and health. Training should not only be directed towards farming communities, but also agricultural and health extension workers. Future riceland mosquito control methods must focus on improving crop productivity and address collective action problems that may occur.